Mechanism and evidence of nonsense suppression therapy for genetic eye disorders. (February 2017) - Richardson, Rose; Smart, Matthew; Tracey-White, Dhani; Webster, Andrew R.; Moosajee, Mariya
Abstract: Between 5 and 70% of genetic disease is caused by in-frame nonsense mutations, which introduce a premature termination codon (PTC) within the disease-causing gene. Consequently, during translation, non-functional or gain-of-function truncated proteins of pathological significance, are formed. Approximately 50% of all inherited retinal disorders have been associated with PTCs, highlighting the importance of novel pharmacological or gene correction therapies in ocular disease. Pharmacological nonsense suppression of PTCs could delineate a therapeutic strategy that treats the mutation in a gene- and disease-independent manner. This approach aims to suppress the fidelity of the ribosome during protein synthesis so that a near-cognate aminoacyl-tRNA, which shares two of the three nucleotides of the PTC, can be inserted into the peptide chain, allowing translation to continue, and a full-length functional protein to be produced. Here we discuss the mechanisms and evidence of nonsense suppression agents, including the small molecule drug ataluren (or PTC124) and next generation 'designer' aminoglycosides, for the treatment of genetic eye disease. Highlights: Mechanism of nonsense suppression therapy. Recent developments in pharmacological nonsense suppression. Evidence of nonsense suppression agents in ocular disease. Implications for the treatment of genetic eye disorders.